Regulation of messenger RNAs for the hydrophobic surfactant proteins in human lung. - Liley, H G; White, R T; Warr, R G; Benson, B J; Hawgood, S; Ballard, P L (The Journal of Clinical Investigation, 1989)
The pulmonary surfactant proteins SP-B (8,000 D) and SP-C (4,000 D) accelerate surface film formation by surfactant phospholipids. We used cDNA probes to examine regulation of these proteins in human fetal lung. The mRNAs were detectable at 13 wk gestation and increased to approximately 50% (SP-B) and approximately 15% (SP-C) of adult levels at 24 wk. The mRNAs were detected only in lung of 11 dog tissues examined. When human fetal lung was cultured as explants without hormones, SP-B mRNA increased and SP-C mRNA decreased. Exposure for 48 h to glucocorticoids, but not other steroids, increased both SP-B mRNA (approximately 4-fold) and SP-C mRNA (approximately 30-fold) vs. controls. Half-maximal stimulation occurred with 1 nM dexamethasone and 300 nM cortisol for SP-B mRNA and at three- to fivefold higher concentrations for SP-C mRNA. Both stimulation and its reversal on removal of hormone were more rapid for SP-B than for SP-C. Terbutaline and forskolin increased SP-B mRNA but not SP-C mRNA. Levels of both mRNAs were much higher in type II cells than fibroblasts prepared from explants. Thus, the genes for SP-B and SP-C are expressed in vivo before synthesis of both SP-A (28,000-36,000 D) and surfactant lipids. Glucocorticoid induction of SP-B and SP-C mRNAs in type II cells appears to be receptor mediated but may involve different mechanisms. Images